2022
DOI: 10.17221/94/2021-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

New product development for mixed beverages of Aceh robusta coffee and cocoa

Abstract: Aceh Province is known by the central production of not only Gayo coffee but also Robusta coffee. They are produced on the southwest coast and east coast for cocoa commodities. Meanwhile, there have been changes in lifestyles, especially in the millennial generation, including at Aceh Province. To reach the opportunity it is very urgent to realise a new product development based on beverages. Focuses of this research were to obtain a coffee-cocoa blend formulation that is suitable for consumers and economical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The statistical analysis revealed that the p value is <0.05 for all the sensory attributes, the null hypothesis is rejected so there is a significant difference among all the sensory characteristics of the coffee powder. Widayat et al (2022) [12] reported that hedonic test assessment was carried out on mixed Aceh's Robusta coffee-cocoa products which covered four aspects: aroma, taste, colour and texture and the result of the study was observed. Statistically, ANOVA did not show a significant difference (p>0.05) among the sensory aspects of flavour, taste, colour and texture among the three variations of formulated coffee powder.…”
Section: Discussionmentioning
confidence: 99%
“…The statistical analysis revealed that the p value is <0.05 for all the sensory attributes, the null hypothesis is rejected so there is a significant difference among all the sensory characteristics of the coffee powder. Widayat et al (2022) [12] reported that hedonic test assessment was carried out on mixed Aceh's Robusta coffee-cocoa products which covered four aspects: aroma, taste, colour and texture and the result of the study was observed. Statistically, ANOVA did not show a significant difference (p>0.05) among the sensory aspects of flavour, taste, colour and texture among the three variations of formulated coffee powder.…”
Section: Discussionmentioning
confidence: 99%
“…In Indonesia, there were many hybrid varieties being developed and further commercial for breeding and the seedlings were originated from diverse countries, e.g. : Ethiopia, Kenya, Middle East, Timor Leste, and South America and they number could reach up to 16 varieties (Widayat et al 2022). However, there is very little information on the magnitude of the up-dated genetic diversity of arabica coffee from Aceh since its early introduction in the late 18th century.…”
Section: Genetic Diversity Of Arabica Coffee In Acehmentioning
confidence: 99%
“…; with the last two are originated from North Sumatra. Usually, those coffees possess the GI certi cates and by having them, this could have more improved their export opportunity at the global market such as by the case of the Arabica Gayo, that has already obtained its certi cate since 2000 (Widayat et al 2022). Moreover, such certi cation would also allow farmers to increase their income possibilities (BRIN 2023).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation